Novel Optimized Functional Yoghurt Made from Soya Bean and Cinnamon - Chancel Hector KENFACK MOMO (Research Perspectives of Microbiology and Biotechnology Vol. 8, 2024)
This study aimed at producing a novel functional soya bean yoghurt by optimizing the production conditions using response surface methodology. The quantity of ferment (LYOFAST Y439A) (50–100 g) and cinnamon (10-40 g) were optimized using a central composite design. This kind of optimization model’s greatest benefit is that it is more specific and eliminates the necessity for a three-level factorial experiment when developing a second-order quadratic model. Responses (global acceptability and scavenging activity) obtained from experimental runs were fitted into second order polynomial regression model. Also, the multiple optimization technic was used to obtain the compromised optimum condition. The optimized yoghurt was evaluated for its pH and proximate composition using standard methods. The optimum conditions for the production of this yoghurt were as thus: 69.64 g for the quantity of ferment and 10 g for the quantity of cinnamon, 100 g soya beans, 100 g of sugar and 1 L of water soybeans. Soy bean yoghurt made from optimized conditions had a global acceptability of 6.8, scavenging activity of 34%. Also, protein, fat, carbohydrate, calcium, sodium, magnesium, and energy value were respectively 17.1%, 2.91%, 17.93%, 144 mg/100 g, 159.91 mg/100g, 63.18 mg/100g and 166.31 kcal/100g. Acceptable yoghurt with functional properties was obtained from soya beans and cinnamon at the end of this study. With its nutrient, antioxidant, and sensory qualities, the newly made soya bean yoghurt offers the consumers possibility to resume eating a healthful diet. The experimental design that was used to get the results can serve as a basis and a guide for setting parameters for the industrial manufacturing scale of more novel functional and healthy yoghurts.